This is because minus times minus is equals plus so the sign must change
Answer:
$14.16
Step-by-step explanation:
4.8 × 2.95. =14.16
I’m pretty sure the 2nd one is the associate property and the 3rd one is the additive inverse property
Hope this helps :)
Answer:
y^6
Step-by-step explanation:
When multiplying terms with exponents that have the same base, the rule is to add the exponents. y * y^3 * y^2 = y^(1 + 3 + 2). (remember that y has a hidden exponent of 1, we just don't write that because it is redundant and unnecessary). y^(1 + 3 + 2) = y^6
hope this helps! <3
(x<span> + </span>9)(x<span> – </span>1<span>) = 0. </span>x<span> = -</span>9<span> or </span>x<span> = </span><span>1</span>